Accelerated dose of Ustekinumab as rescue therapy in acute severe ulcerative colitis - Nik Muhamad Affendi, Nik Arsyad; Choon, Jin Ooi; hilmi, ida normiha (2022)
We report a first case to our knowledge of acute severe ulcerative colitis (ASUC) which was successfully treated with off label accelerated ustekinumab monotherapy. A 75-year-old man with recently diagnosed ulcerative colitis (UC) on mesalazine, ischemic heart disease, congestive heart failure (CCF), diabetes and chronic obstructive pulmonary disease (COPD) presented with bloody diarrhoea 6 times/day, severe lethargy and fever. On examination, his temperature was 38°C, pulse rate was 90 beats per minute, blood pressure was 128/68 mmHg, abdomen was soft but mildly tender. Haemoglobin was 91 g/dL, albumin was 23 g/L, C-reactive protein was 144 mg/L and CT abdomen showed diffuse colonic thickening but no dilatation. Unprepared left flexible sigmoidoscopy showed severe inflammation with deep ulceration (Figure 1). Clostridioides difficile and Cytomegalovirus (CMV) were ruled out. He was started on intravenous hydrocortisone 100mg qid but did not achieve adequate response and his diabetic control worsened. Although he was referred to the surgeons, he refused surgery. We were reluctant to start him on infliximab or cyclosporin because he has a high risk of infection as well as CCF and opted for ustekinumab in view of the more favorable side effect profile and relatively rapid onset of action. He was given an intravenous loading dose of 390mg followed by 90mg subcutaneous dose at week 2 and 6 with subsequent 8-weekly maintenance. He was in clinical remission by week 4 and repeat colonoscopy at week 24 showed complete mucosal healing with pseudopolyps and scar formation (Figure 2). Although infliximab or cyclosporin is the established rescue therapy for ASUC1, the older adult patient is at risk of significant adverse events from these therapies. Studies have shown that infliximab and cyclosporin can increase risk of infection and mortality in the elderly.2,3 Infliximab is also contraindicated in stage III/IV CCF.3 In view of this, we opted for ustekinumab although there is no data regarding its use in this setting. However, biologic clearance is much higher in ASUC, therefore accelerated therapy in often needed.5,6 We used the accelerated dose ustekinumab based on a few studies which showed that shortened dose interval of 2-weekly was safe.7,8 Our case highlights the potential efficacy of ustekinumab in treatment of ASUC in high-risk groups, but more data is required to recommend this approach over the current established therapies.